Analysis of Factors Affecting Clean Water Service in Dili City - Gomes, Orlando; Wulandari, Esti; Nugroho, Laksono Djoko (Transpublika Publisher, 2025)
Availability of clean water is a basic need in Dili City, Timor Leste, but uneven distribution, inadequate infrastructure, and limited resources are the main challenges. This study aims to analyze the factors that influence clean water services. The research method included multiple linear regression analysis to identify influential factors. Data was obtained through surveys, interviews, official reports and literature review. The results showed that piping distance and number of family members positively influenced water quality and quantity, while household income tended to decrease water quality and quantity. Expenditure on clean water improves water quality and quantity. For water continuity, the number of people in the family had a strong positive effect, while other factors had a negative effect. The coefficient of determination for water quality is 5.3%, water quantity 20.9%, and water continuity 5.9%, indicating that many other factors influence water services in Dili City.